Impact of intrahepatic cholestasis of pregnancy on neonatal respiratory outcomes (CHOLE-RESP): protocol for a prospective cohort study - Niculae, Lucia Elena; Niculae, Alexandru Stefan; Tocariu, Raluca; Petca, Aida (Frontiers in Pediatrics, 2026)
BackgroundIntrahepatic cholestasis of pregnancy (ICP) is the most common liver disorder unique to pregnancy, associated with elevated maternal bile acid concentrations and adverse perinatal outcomes.MethodsThis is a prospective cohort study conducted in a level III neonatal unit in Bucharest, Romania. Neonates born to mothers with ICP (serum bile acids ≥10 μmol/L within seven days before delivery) will be enrolled alongside gestational age, sex and birthweight-matched controls. Serum samples will be collected at 24 h, 48–72 h and on day 7 of life. Quantitative ELISA kits will be used to assess serum biomarkers associated with surfactant dysfunction and lung injury. Perinatal and clinical outcomes will be recorded systematically.ResultsThe primary aims are to compare the incidence of respiratory distress syndrome (RDS), the need for surfactant administration and serum biomarker profiles between ICP-exposed and unexposed neonates. Secondary aims include evaluating respiratory support requirements, neonatal morbidity and mortality across groups.ConclusionsWe expect that neonates exposed to maternal cholestasis will have a higher incidence of RDS, increased surfactant need, and biomarker alterations consistent with pulmonary compromise. This study may improve understanding of bile acid-related lung injury and inform early risk stratification strategies in affected newborns. (NCT06679972).